Nursing management of a patient with hydrocele of tunica vaginalis and lesions in the epididymis (1例睾丸鞘膜积液并附睾肿物的护理) - SONG Ying (宋樱) (Association of Integrative Nursing, 2021)
This paper reviewed the clinical data of a patient with hydrocele of tunica vaginalis and lesions in the epididymis. In addition to the psychological care and pain control, targeted nursing interventions on dysuresia, rehabilitation guidance and health education were carried out. (本文回顾1例睾丸鞘膜积液并附睾肿物患者的临床资料, 总结相关护理经验。护理人员在开展心理支持疏导、疼痛护理干预的基础上, 针对排尿困难症状实施对症护理措施, 同时加强康复指导及健康教育。)